VARIATION IN REJANG LANGUAGE - Zakaria - (Holistics (Hospitality and Linguistics) : Jurnal Ilmiah Bahasa Inggris, 2010)
This paper was written to find out the variation in Rejang language which cover Rejang Kepahiang (RK), Rejang Lebong (RK) and Rejang Curup (RC). The aspects consist of phonological, morphological and semantic level that were viewed from descriptive ways. The result shows that it is difficult to predict how a particular language user speaks in a certain social context. It is linguistically caused by Rejang language and also influenced by the speakers, addresses, age, setting and context when the communication takes place.